Strategi Guru Agama Desa dalam Meningkatkan Kemampuan Membaca Al-Qur’a Warga Desa - Joni, Rama; Rahman, Abdul; Yanuarti, Eka (JOEAI (Journal of Education and Instruction), 2020)
This study aims to explore and find out the strategies of village religious teachers in improving the ability to read the Koran of Turan Baru villagers especially those aged 40 years and older. By using descriptive qualitative writing methods, data obtained using interviews and observations. The informants in this study were religious teachers and students studying the Koran in the village of Turan Baru. The results of the study obtained information that there are several strategies implemented by the Turan Baru Village Religion Teachers to improve the students' ability to read the Qur'an, namely; routine recitation; strategies for listening and correcting santri readings during recitation; motivate students in learning to read the Qur'an. The listening strategy used by village religious teachers is still quite effective in improving the ability to read Al-Qur'an of pilgrims who are above the age of 40 years and above, because when there is an error the teacher can immediately correct the mistakes of the congregation. Conclusions, methods and listening strategies in reading the Qur'an in the village of Turan Baru is one way to improve the ability to read the Qur'an, this strategy also increases the enthusiasm of learning of the congregation, which will eventually bring the congregation the better in reading the Qur'an with the correct reading rules. Keywords: Strategy, Village Religion Teachers, Al-Qur'an Reading Ability